Drobisch's Legacy to Price Statistics - Ludwig von Auer (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2010)
In order to provide information concerning the significant contributions to price index theory made by Moritz Wilhelm Drobisch (1802-1896), this paper presents an account of his pioneering scientific achievements together with a synopsis of his personal and professional life. He was the first to formulate the unit value index as well as the Laspeyres and Paasche price indices. These three indices are the key for the official inflation measurements that are made around the world today.
Keywords: C43; E31; E52; 330; Price; Inflation; Index Theory; Measurement